The association of pattern of lifetime alcohol use and cause of death in the European prospective investigation into cancer and nutrition (EPIC) study. - Bergmann, M; Rehm, J; Klipstein-Grobusch, K; Boeing, H; Schütze, M; Drogan, D; Overvad, K; Tjønneland, A; Halkjær, J; Fagherazzi, G; Boutron-Ruault, M; Clavel-Chapelon, F; et al. (2013)
BACKGROUND: There is limited evidence for an association between the pattern of lifetime alcohol use and cause-specific risk of death. METHODS: Multivariable hazard ratios were estimated for different causes of death according to patterns of lifetime alcohol consumption using a competing risks approach: 111 953 men and 268 442 women from eight countries participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) study were included. Self-reported alcohol consumption at ages 20, 30, 40 or 50 years and at enrollment were used for the analysis; 26 411 deaths were observed during an average of 12.6 years of follow-up. RESULTS: The association between lifetime alcohol use and death from cardiovascular diseases was different from the association seen for alcohol-related cancers, digestive, respiratory, external and other causes. Heavy users (>5 drinks/day for men and >2.5 drinks/day for women), regardless of time of cessation, had a 2- to 5-times higher risk of dying due to alcohol-related cancers, compared with subjects with lifetime light use (≤1 and ≤0.5 drink/week for men and women, respectively). Compared with lifetime light users, men who used <5 drinks/day throughout their lifetime had a 24% lower cardiovascular disease mortality (95% confidence interval 2-41). The risk of death from coronary heart disease was also found to be 34-46% lower among women who were moderate to occasionally heavy alcohol users compared with light users. However, this relationship was only evident among men and women who had no chronic disease at enrollment. CONCLUSIONS: Limiting alcohol use throughout life is associated with a lower risk of death, largely due to cardiovascular disease but also other causes. However, the potential health benefits of alcohol use are difficult to establish due to the possibility of selection bias and competing risks related to diseases occurring later in life.